НЕМИС ТИЛИ САБАҒЫНДА ОҚЫЎШЫЛАРДЫҢ ЕРКИН ПИКИРЛЕЎ УҚЫПЛЫЛЫҒЫН РАЎАЖЛАНДЫРЫЎДА ПЕДАГОГИКАЛЫҚ ТЕХНОЛОГИЯЛАРДЫҢ ӘҲМИЙЕТИ - Есбергенова, Г.Б. (ILIM hám JÁMIYET, 2022)
In the article the gist of pedagogical technologies are discussed in teaching the foreign languages in current elementary classes. As well, the interactive methods are recommended in the process of teaching and the due competencies of teachers.